Evaluasi Postur Kerja Pada Unit Integrated Operation Center Regional (Iocr) Pt Abc Menggunakan Metode Rapid Office Strain Assesment (Rosa) - A'SYAROH, INSAN KHUSNULAILAH, ETIKA MUSLIMAH, ST.,MT (2016)
PT ABC is the company in services in an activity his job use computers .The department of integrated operation center regional ( IOCR ) is the department of who use a computer in his job to handle a customer complaint . Activity work IOCR that is received a call and typing. Of computer use to the department IOCR the average 24 hours a day. The increasing number of the use of computers not followed by concern users to the ergonomics when been working with computers. Been working with the computer by not seen with ergonomics can cause fatigue of body, changing the form of bone structure, musculoskeletal disorder and others, but the high complaints workers can be influenced by facilities factor, the layout work and workplace. Employees feel complaints neck the bottom of a total of 58 %, the left shoulder about 58 % and loins about 67 %. Complaints on employees can be reduced by evaluate posture verb that does not ergonomic and give the act of repairing. Evaluation posture work can be done by using the method ROSA (Rapid Office Strains Assessment). Risk factors from the use of computers divided into seats, monitor, phone, keyboard and mouse. Way assessment ROSA namely by conducting assessment increased 3-1 of any risk factors work. The final result assessment ROSA to be obtained those scores range between 1-10, if final score obtained greater than 5, so the job considered risky. In addition duration of time work have also been considered. Based on the assessment ROSA obtained value risk of 6 from as many as 12 people. The results of more than 5 and included in the occupation category are at risk, then required the act of repairing. Keywords: IOCR (Integrated Operation Center Regional), Ergonomics, ROSA (Rapid Office Strains Assessment).